Optimal t_f and t_0 as function of A (Re=2000,Wo=15) - Duo Xu; Baofang Song; Marc Avila (PANGAEA, 2022)
The data are obtained via an in-house Matlab script (developed by Dr. Baofang Song) to compute the non-modal transient growth of disturbances in pulsatile and oscillatory pipe flows. In this study, a Newtonian fluid driven by pulsatile and oscillatory flow rate flows in a straight pipe. In pulsatile flow, there are three governing parameters: steady Reynolds number (defined by the steady flow component), pulsation amplitude (ratio of oscillatory and steady flow component) and Womersley number (dimensionless pulsation and oscillation frequency). In oscillatory flow, due to vanishment of steady flow component, oscillatory Reynolds number (defined by the oscillation flow component) and Womersley number. The Reynolds number defined by the thickness of Stokes layer is alternatively used for the oscillatory Reynolds number. The study was carried out in a manner that one governing parameter varies while other governing parameters are fixed. The data file extquotesinglet0_tf_A.dat extquotesingle shows the variation of optimal time (corresponding to the maximum energy amplification) with the pulsation amplitude for the Reynolds number of 2000 and the Womersley number of 15. This file includes four columns: the first column indicates the pulsation amplitude; the second column indicates the initial time of perturbations normalized by pulsation period; the third column indicates the evolution time of the perturbation normalized by period; the fourth column indicates the final time normalized by the period.